Thermal analysis on PCB using Galerkin approach - Che Soh, Mohd Norhisham; Bugis, Ismadi; Jamaludin, Irma Wani; Ranom, Rahifa (2011)
This paper presents the analysis of temperature rise on PCB. Numerical solutions using Galerkin approach that is one of Finite Element Method (FEM) was used to study and analyze the temperature rise on PCB. Then, an algorithm has been developed using MATLAB. The PCB with four different width of copper is supplied with different range of direct current (DC) from 0.5 to 5 Amperes to capture the data by using FLIR i5 Infrared Thermal Imager. The data then compared with numerical result and obtain an error. In order to minimize the error, an analysis is done based on Galerkin approach with heat transfer film coefficient obtained from the experiment. The numerical results showed good agreement with the experimental results and it can be proved that the algorithm developed based on Galerkin approach can be applied to the thermal analysis on PCB.